1998
DOI: 10.1172/jci1567
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid exposure in late gestation permanently programs rat hepatic phosphoenolpyruvate carboxykinase and glucocorticoid receptor expression and causes glucose intolerance in adult offspring.

Abstract: Low birth weight in humans is predictive of insulin resistance and diabetes in adult life. The molecular mechanisms underlying this link are unknown but fetal exposure to excess glucocorticoids has been implicated. The fetus is normally protected from the higher maternal levels of glucocorticoids by feto-placental 11 ␤ -hydroxysteroid dehydrogenase type-2 (11 ␤ -HSD2) which inactivates glucocorticoids. We have shown previously that inhibiting 11 ␤ -HSD2 throughout pregnancy in rats reduces birth weight and cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

41
536
16
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(604 citation statements)
references
References 66 publications
41
536
16
11
Order By: Relevance
“…Vuguin et al (31) reported an elevated basal hepatic glucose production in normoglycemic intrauterine growth-retarded rats compared with control rats, indicating that uteroplacental insufficiency causes a primary defect in hepatic metabolism before the onset of overt hyperglycemia. Another study in animals demonstrated that an adverse intrauterine environment induced by dexamethasone resulted in overexpression of hepatic PEPCK and increased gluconeogenesis (32). Furthermore, maternal hypoxia (33) and protein deprivation (34) during pregnancy resulted in overexpression of PEPCK and downregulation of glucokinase, with the net effect of inappropriately elevated hepatic glucose production.…”
Section: Discussionmentioning
confidence: 99%
“…Vuguin et al (31) reported an elevated basal hepatic glucose production in normoglycemic intrauterine growth-retarded rats compared with control rats, indicating that uteroplacental insufficiency causes a primary defect in hepatic metabolism before the onset of overt hyperglycemia. Another study in animals demonstrated that an adverse intrauterine environment induced by dexamethasone resulted in overexpression of hepatic PEPCK and increased gluconeogenesis (32). Furthermore, maternal hypoxia (33) and protein deprivation (34) during pregnancy resulted in overexpression of PEPCK and downregulation of glucokinase, with the net effect of inappropriately elevated hepatic glucose production.…”
Section: Discussionmentioning
confidence: 99%
“…In humans it is known that prenatal exposure to prednisone or maternal Cushing's syndrome is associated with intrauterine growth retardation (IUGR) [11,12]. In rodents, fetal exposure to glucocorticoids induces IUGR at birth, and impaired glucose tolerance [13][14][15] and hypertension [16,17] at adult age. Numerous studies have investigated the deleterious effects of glucocorticoids on pancreatic beta cell function, showing altered glucosestimulated insulin release, both in vitro in islets treated with dexamethasone [18][19][20] and in vivo in mice overexpressing GR in the beta cells [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Porém, aos 10 dias de idade, apenas os filhotes nascidos das fêmeas tratadas por 14 dias apresentaram aumento significativo da concentração sérica de carboidratos totais em relação aos das ratas do grupo-controle. Isto pode estar relacionado ao potencial da dexametasona em induzir o desenvolvimento da resistência insulina em ratos jovens (Nyirenda et al, 1998), pois, nos primeios dias de vida, a glicemia em ratos sofre grandes variações, em parte atribuídas a alterações abruptas no teor de enzimas responsáveis pela disponibilização da glicose hepática para o sangue, sendo a resistência à insulina um fator intensificador desse efeito (Carvalheira, 2002).…”
Section: Discussionunclassified
“…Durante a gestação, o transporte transplacentário de glicocorticoides é regulado pelas enzimas 11β-hidroxiesteroide desidrogenase (11β-HSD) tipo 1 e 2, que atuam na reativação e inativação de glicocorticoides, respectivamente, regulando a exposição do feto a esses fármacos (Diederich et al, 2002). Devido à progressiva redução da bioatividade da enzima 11β-HSD2 ao longo da gestação (Waddell et al, 1998), o terço final é o período de gestação em que ocorre maior permissibilidade do tráfego de glicocorticoides, levando a alterações fisiológicas, como a elevação do nível glicêmico pós-natal, a redução da síntese de receptores para insulina e a mobilização de glicogênio para a corrente sanguínea (Nyirenda et al, 1998).…”
unclassified